Iz sodnikovih v tožilčeve roke? - Mihelj Plesničar, Mojca (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2013)
Plea bargaining is an alien in continental criminal procedures and brings about plenty of important issues. The discussion in this article revolves around such issues as they relate to the questions of punishment and sentencing. Two main notions are dealt with in this respect: First, I examine the relationship between plea bargaining and one of the cornerstone principles of punishment in continental systems the individualisation of punishment. Secondly, the wider question regarding the changing role of the prosecution is addressed, mainly from the viewpoint of shifting responsibility and authority with regard to sentencing from the judiciary to the prosecution.
Keywords: kazenski postopek; kazenske sankcije; pravosodje; sodniki; tožilstvo; pogajanje; krivda; priznanje